Energy dissipation balanced and reliable clustering algorithm for wireless sensor networks - Jun YUE; Wei-ming ZHANG; Wei-dong XIAO; Da-quan TANG; Jiu-yang TANG (Tongxin xuebao)
A novel clustering algorithm for wireless sensor networks was proposed to resolve the hot spot problem and the single failure problem.The algorithm divided the network into unequal grids,and the nodes in the same grid form a cluster.The number of cluster heads in each grid was determined according to the failure probability of nodes,and the data collection of nodes in a grid was implemented by multiple cluster heads of the grid cooperatively.By adjusting the number of nodes that could participate in cluster head rotation of each grid,the algorithm was able to balance the energy dissipation of nodes on a long view.The algorithm reduced the reliance of cluster members to single cluster head by forming cluster with multiple cluster heads.Furthermore,the algorithm adopted some measures to diminish energy consumption.Simulation results show that the algorithm has higher balanced extent of energy dissipation and reliability of data collection,and prolongs the lifetime of network.